2013
DOI: 10.1111/soin.12021
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Effects of Racially Homophilous Sponsorship Ties on Job Opportunities in an Elite Labor Market: The Case of NCAA Basketball Coaching

Abstract: We examine how an assistant coach's race and the race of his supervisor (the head coach) interact to affect future job quality. While past research argues that homophily is beneficial to job mobility, we find differential effects based on the race. OLS and OLR regression analyses on the quality of one's first head coaching job in NCAA men's basketball indicate that black assistant coaches working under black head coaches (black homophily) are significantly disadvantaged compared to all other racial combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
(51 reference statements)
1
20
0
Order By: Relevance
“…Doing this advances the literature on employability resilience by examining how race and homophily affect employment during periods of job instability. In line with Seebruck and Savage (2014), we view the racial pairings in this labor market to be homophily or heterophily (i.e., processes) rather than merely homogeneity or heterogeneity (i.e., states of being) because head coaches have agency over the selection of their assistant coaches. Halgin (2009:2) defined employability resilience as "success in finding desirable new positions after being fired."…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Doing this advances the literature on employability resilience by examining how race and homophily affect employment during periods of job instability. In line with Seebruck and Savage (2014), we view the racial pairings in this labor market to be homophily or heterophily (i.e., processes) rather than merely homogeneity or heterogeneity (i.e., states of being) because head coaches have agency over the selection of their assistant coaches. Halgin (2009:2) defined employability resilience as "success in finding desirable new positions after being fired."…”
mentioning
confidence: 87%
“…However, research on the effects of homophily on job outcomes for college coaches finds that homophily is not universally beneficial for career mobility (Day and McDonald 2010;Seebruck and Savage 2014). For instance, Day and McDonald (2010) found that in college football coaching, black-black homophily negatively affected the likelihood of promotion.…”
Section: The Effects Of Race and Racial Homophilymentioning
confidence: 99%
See 1 more Smart Citation
“…Homophily has also been successfully used to understand the persistence of racial inequalities in the workplace. Seebruck and Savage () reveal that while homophily may not in itself advantage White employees, it does disadvantage ethnic minority employees. However, homophily may be advantageous for marginalised people when they enter social networks, including those from ethnic minority backgrounds (Mollica et al, )…”
Section: Homophily and Social Networkmentioning
confidence: 99%
“…At the highest level of college football, white coaches are more likely than black coaches to be hired to the most prestigious coaching positions (Bozeman and Fay ; Cunningham and Bopp ). Current black college basketball coaches do not receive the same opportunities as white coaches (Cook and Glass ; Seebruck and Savage ). In addition, media narratives still emphasize blacks’ superior athleticism and highlight white players’ intelligence and work ethic (Granger, Newman, and Andrews ).…”
Section: Review Of the Literaturementioning
confidence: 99%